Sustainable Deficit Irrigation Technique to Enhance “KEITT” Mango Productivity in a Semi-Arid Climate Region - Ahmed Kamal; Abdel Ghany El-Gindy; Khaled elbagoury; Bahaa Sayed (Arab Universities Journal of Agricultural Sciences)
Water scarcity necessitates the implementation of various strategies to manage irrigation processes, aiming to optimize water usage for sustainable development, particularly in Semi-Arid regions. This research investigates the impact of using a sustainable deficit irrigation (SDI) technique alongside a drip irrigation system on the efficiency of water use and the growth and productivity of "KEITT" mango trees. The experiment examined four levels of irrigation requirements (IR) at 50%, 60%, 75% and 100%, using four different dripper spacing distances (60, 50, 40 and 30 cm). The average tree productivity during the 2022 season was 26.060, 24.100, 25.740 and 24.330 kg/tree, respectively, while in the 2023 season, it was 25.940, 24.760, 25.250 and 24.380 kg/tree. The average water use efficiency (WUE) values were 4.950, 3.880, 3.240 and 2.320 kg/m³ for the 50%, 60%, 75% and 100% IR treatments, respectively. The results indicated no significant differences in the growth and productivity of the mango crop across different irrigation levels. It was found that irrigating at 50% IR achieved the highest water use efficiency, saving more than 3500 m³ of water per fedden per season. These findings suggest that policymakers can adopt sustainable deficit irrigation techniques to enhance WUE without compromising crop productivity.